DNA conformations and their sequence preferences - Svozil, Daniel; Kalina, Jan; Omelka, Marek; Schneider, Bohdan (Nucleic acids research, 2008)
The geometry of the phosphodiester backbone was analyzed for 7739 dinucleotides from 447 selected crystal structures of naked and complexed DNA. Ten torsion angles of a near-dinucleotide unit have been studied by combining Fourier averaging and clustering. Besides the known variants of the A-, B- and Z-DNA forms, we have also identified combined A + B backbone-deformed conformers, e.g. with alpha/gamma switches, and a few conformers with a syn orientation of bases occurring e.g. in G-quadruplex structures. A plethora of A- and B-like conformers show a close relationship between the A- and B-form double helices. A comparison of the populations of the conformers occurring in naked and complexed DNA has revealed a significant broadening of the DNA conformational space in the complexes, but the conformers still remain within the limits defined by the A- and B- forms. Possible sequence preferences, important for sequence-dependent recognition, have been assessed for the main A and B conformers by means of statistical goodness-of-fit tests. The structural properties of the backbone in quadruplexes, junctions and histone-core particles are discussed in further detail.
Keywords: DNA vazebné proteiny; Nucleic Acid Conformation; Base Sequence; G-kvadruplexy; cytosin; RNA; DNA; G-Quadruplexes; nukleozomy; DNA-Binding Proteins; DNA, A-Form; konformace nukleové kyseliny; A-DNA; Nucleosomes; Cytosine; deoxyribonukleotidy; ligandy; křížová struktura DNA; DNA, Cruciform; Ligands; Deoxyribonucleotides; sekvence nukleotidů